THE DEVELOPMENT OF GASTROINTESTINAL TRACT’S INVASIVE ORIGIN OF STRONGYLIDAE IN ENVIRONMENT - R. H. Gayrabekov; L. A. Altamirova; M. M. Salmanova; A. K. Sharipova (Юг России: экология, развитие, 2014)
Survival of the ovums, of the larvas and of the invasion larvas of strongylates in environment depends on many conditions. This biological process was investigated by us in experimental conditions.